UPAYA PENCEGAHAN DAN PENANGANAN KASUS HUMAN TRAFFICKING DI INDONESIA PASCA RATIFIKASI ASEAN CONVENTION AGAINST TRAFFICKING IN PERSONS, ESPECIALLY WOMEN AND CHILDREN (ACTIP) TAHUN 2017 - Arwita Razdkyta, (2022)
Indonesia as one of the countries in Southeast Asia that is a source, transit and destination country for human trafficking has also taken various actions to prevent and deal with the problem of human trafficking, one of which is by ratifying the ASEAN convention, namely the ASEAN Convention Against Trafficking in Persons, Especially Women. and Children (ACTIP) in 2017. This study aims to find out the various efforts made by Indonesia as a form of ratification of ACTIP. This research is qualitative with a descriptive model and uses the theory of human trafficking, international regimes, and regional leadership, and uses internet-based research and literature studies in data analysis techniques. The results of this study indicate that various efforts made by the Indonesian government, both domestically and internationally, are able to reduce the number of victims of human trafficking and increase responsiveness in providing assistance to victims.